2015
DOI: 10.1142/s1793545815500352
|View full text |Cite
|
Sign up to set email alerts
|

Pasting properties by near-infrared reflectance analysis of whole grain paddy rice samples

Abstract: A rapid predictive method based on near-infrared re°ectance spectroscopy (NIRS) of paddy rice was developed to measure the pasting properties of rice. The paddy rice samples were scanned by a near-infrared re°ectance spectrometer in the wavelength region of 1400-2400 nm and preprocessed by mathematical pretreatments prior to pasting properties analysis using a rapid visco-analyzer (RVA). The results indicated that the developed models of setback (SB), peak viscosity (PV), breakdown (BD) and consistency (CS) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
6
5
0
Order By: Relevance
“…The absorption peaks at wavelengths of 1,566 nm with correlation coefficients ( R ) of 0.98, 1,752 nm with R of 0.988 and 2,100 nm with R of 0.93 for flour samples, also, the absorption peaks at 1,566 nm with R of 0.67 and 2,295 with R of 0.70 for rice samples can be attributed to the SBV, the results from the reported research are in agreement with the ones obtained by Siriphollakul et al. (2015) because the correlation coefficients reported by him, around (0.81–0.96), were quite similar to the ones from this research. Also, the absorption peak at 997 nm with R of 0.73 for flour samples, also, the absorption peak at 997, 1,199, 1,456, 1,566, and 1,750 nm with R of (0.91, 0.99, 0.98, 0.98, and 0.983), respectively, for rice samples could be correlated with the BDV, this results was according to that obtained by Natsuga and Kawamura (2006) who observed that the correlation coefficients of the parameter BDV for milled rice were 0.91.…”
Section: Pls Models and Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The absorption peaks at wavelengths of 1,566 nm with correlation coefficients ( R ) of 0.98, 1,752 nm with R of 0.988 and 2,100 nm with R of 0.93 for flour samples, also, the absorption peaks at 1,566 nm with R of 0.67 and 2,295 with R of 0.70 for rice samples can be attributed to the SBV, the results from the reported research are in agreement with the ones obtained by Siriphollakul et al. (2015) because the correlation coefficients reported by him, around (0.81–0.96), were quite similar to the ones from this research. Also, the absorption peak at 997 nm with R of 0.73 for flour samples, also, the absorption peak at 997, 1,199, 1,456, 1,566, and 1,750 nm with R of (0.91, 0.99, 0.98, 0.98, and 0.983), respectively, for rice samples could be correlated with the BDV, this results was according to that obtained by Natsuga and Kawamura (2006) who observed that the correlation coefficients of the parameter BDV for milled rice were 0.91.…”
Section: Pls Models and Resultssupporting
confidence: 92%
“…Also, similar observations were reported by Siriphollakul et al. (2015) who reported that the RPD of the parameters BDV and SBV for grain paddy rice samples were 2.14 and 3.12, respectively. Also, this result was according to that obtained by Natsuga and Kawamura (2006) who reported that the RPD of the parameters PC were 2.9.…”
Section: Pls Models and Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For this purpose, much attention has been focused on near-infrared reflectance spectroscopy (NIRS) as an alternative option to traditional means. A number of studies have shown that NIRS has the potential to be used as a quick procedure for predicting the quality properties involving amylose content, protein content, and other grain quality traits [ 19 , 20 , 21 , 22 ]. However, weak absorption of overtone and combination, broad bands and lack of characteristics are typical of NIRS, thus making NIRS calibration models largely dependent on chemometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of gelatinized starch, several important physical changes occur in rice which play an important role in the next processing operations of rice. For example, it would be effective storage, milling, and cooking quality (Bhattacharya, 2011;Hu et al, 2017;Roy et al, 2011;Siriphollakul et al, 2015;Yu et al, 2017). Depending on the variety of rice, water temperature and duration of soaking, steaming time, temperature and pressure, drying time and temperature and other factors related to the rice parboiling, show different physical properties and so several quality.…”
Section: Introductionmentioning
confidence: 99%